2012
DOI: 10.1111/j.1469-0691.2012.03881.x
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus among companion and food-chain animals: impact of human contacts

Abstract: Clin Microbiol Infect 2012; 18: 626–634 Abstract Methicillin‐resistant Staphylococcus aureus (MRSA), one of the major pathogens in humans, is a cause of infection and colonization among animals. The increasing number of companion animals and antibiotic use have made this population a reservoir of MRSA. In parallel, the evolution of new MRSA clones and mec homologues among animals of the food chain has emphasized the need for infection control practices in animals and humans in close contact. On the basis of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 110 publications
0
67
0
Order By: Relevance
“…It is also possible that the handlers of the birds transferred the organisms to the birds. Reports have shown that MRS can be transferred from humans, especially animal handlers, to animals on direct and/or indirect contact (Petinaki and Spiliopoulous, 2012). However, colonization of the cloacae of the birds may have resulted following ingestion of the MRS from contaminated litter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the handlers of the birds transferred the organisms to the birds. Reports have shown that MRS can be transferred from humans, especially animal handlers, to animals on direct and/or indirect contact (Petinaki and Spiliopoulous, 2012). However, colonization of the cloacae of the birds may have resulted following ingestion of the MRS from contaminated litter.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is an increasing numbers of reports on the isolation of LA-MRS from humans, farm and slaughterhouse environments and animals (Mulders et al, 2010;Petinaki and Spiliopoulous, 2012). This necessitated surveillance studies to assess food-producing animals as potential reservoirs of MRS in different parts of the world such as America (Smith et al, 2008;Waters et al, 2011), Europe (Armand-Lefevre et al, 2005Friese et al, 2012;Huijsdens et al, 2006;Meemken et al, 2008;Pomba et al, 2009;Voss et al, 2005;), Asia (Lee, 2003;Moon et al, 2007) and South Africa (Ateba et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, MRSA were isolated from the milk of dairy cows with mastitis in Belgium [12]. Reports of MRSA in livestock and humans in close contact provided evidence of LA-MRSA spread throughout Europe, Canada, the USA, China, Malaysia and Korea [12].…”
Section: La-mrsa and Companion Animalsmentioning
confidence: 99%
“…Reports of MRSA in livestock and humans in close contact provided evidence of LA-MRSA spread throughout Europe, Canada, the USA, China, Malaysia and Korea [12]. LA-MRSA have specific genotypic and phenotypic characteristics: namely nontypeability by PFGE of SmaI DNA digests, the majority belong to CC398 recovered from pigs, they carry different SCCmec elements, they often exhibit resistance to many nonb-lactam antimicrobials (used in animal production) and they lack toxins gene carriage.…”
Section: La-mrsa and Companion Animalsmentioning
confidence: 99%
“…But in the beginning of 2000, community-acquired MRSA also started to be reported (2). MRSA-related osteomyelitis (1), nasopharyngeal colonization (3), skin infections (4), food-chain animal infections (7), and infections in immunocompromised patients (8), among others, were reported. Resistance mechanisms were reviewed previously (5,9,10).…”
mentioning
confidence: 99%